The Darjeeling Limited [videorecording (DVD)] - Anderson, Wes, 1969-; Wilson, Owen, 1968-; Brody, Adrien; Karan, Amara, 1984-; Murray, Bill, 1950 September 21-; Huston, Anjelica (20th Century Fox Home Entertainment, 2008)
Having not spoken to each other in a year, three American brothers set off on a train voyage across India with a plan to find themselves and bond with each other. The brothers wanted to regain their friendship of each other. Their "spiritual quest," however, veers rapidly off-course - thanks in part to over-the-counter pain killers, Indian cough syrup, and pepper spray. Eventually the three find themselves stranded alone in the middle of the desert with eleven suitcases, a printer, and a laminating machine. From this point forward, an unplanned journey begins.